(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It can be observed that theproduction of small scale industries which was Rs. 78,882 crore in 1990-91,rose upto a level of Rs. 6,95,126 cr., indicating a growth of nine times injust 18 years. The table shows that this sector was giving employment to 158.34lakhs of people in 1990-91, this employment increased to a level of 322.28lakhs in 2007-08. The percentage growth rate which was just 2.3 percent overlast year in 1991-92 went upto 18.3 percent in 2007-08. The study furtherbrings out the impact of liberalization on growth in number of units,employment level in SSI sector, production (at constant prices), fixedinvestment and the value of plant and machinery from the year 1981 to year2008. The data in regard to share of SSIs in total exports from India arepresented in Table. It is obvious from the table that contribution of SSIsector in the total exports from India during pre-liberalization period hadranged from 22 to 29 per cent. However, its share rose to 30 percent in 1990-91and 36.4 percent in 1993-94. However, its share came down slightly in nextthree years. The share in exports went up to 38.2 percent in the year 1997-98.What attracts our attention is the stagnation in the percentage share of SSIsector in the total exports during the recent years. That is, the percentageshare of SSI in the total exports has been hovering between 33 to 35 percentsince 1999. Table 4.3 also exhibits that total exports have registeredrelatively